CHARACTERISTICS, RANKING, AND POTENTIAL OF COAL ON SEAM H AND SEAM H2 - RIZKY, ALIF DILANDY; Nurdrajat, Nurdrajat; Hardiyono, Adi; Salinita, Silti (Journal of Geological Sciences and Applied Geology, 2023)
Coal is a complex solid object consisting of several chemical elements and comes from plants that are deposited in a basin. The South Sumatra Basin is a basin with the presence of the Muara Enim Formation which is known as a coal-bearing formation. In this research, secondary data was used in the form of proximate analysis, ultimate analysis, and combustion properties analysis results in determining the characteristics, ranking, and potential of coal in the research area. Based on ASTM D 388 – 05 classification, coal in seam H has a Subbituminous B Coal ranking, while seam H2 has a Subbituminous A Coal rating. Based on the parameters in assessing the coal potential use for coal-fired power plants according to Thomas, 2013 in Suhat, et al., 2020, coal in seam H and seam H2 does not support the utilizations, but solutions can be carried out in the form of rewashing sample, coal drying, and coal blending.